Developing Speaking Skills in Arabic Learners who are Non-Native Speakers: A Descriptive and Analytical Study: تطوير مهارة التحدث عند متعلمي اللغة العربية للناطقين بغيرها: دراسة وصفية تحليلية - Faryat, Amar; Ahmiani, Otman (Institut Agama Islam Negeri Palangka Raya, 2025)
This study explores the development of speaking skills among Arabic language learners who are non-native speakers, considering it a fundamental skill for achieving effective communication that allows learners to participate confidently in various life situations. The research emphasizes the importance of the interactive aspect of teaching, drawing on social and cultural theories that view interaction as a key means of language acquisition. The study presents the various challenges faced by learners, including linguistic difficulties, cultural gaps, and the fear of making mistakes, and proposes a range of solutions to address these challenges, such as adopting interactive activities, promoting active listening, and providing constructive feedback. It also recommends the use of modern technology to create a communicative environment that transcends the limits of the traditional classroom, offering learners opportunities to interact with native Arabic speakers in diverse ways. The study further advocates for the development of educational programs that consider cultural diversity and integrate Arabic culture into the educational content, aiming to enhance learners' understanding of the linguistic and cultural context, which in turn helps build their confidence when speaking, in line with the guidelines of the American Council on the Teaching of Foreign Languages.